2021
DOI: 10.1038/s41598-021-90362-9
|View full text |Cite
|
Sign up to set email alerts
|

High plasma concentration of non-esterified polyunsaturated fatty acids is a specific feature of severe COVID-19 pneumonia

Abstract: COVID-19 pneumonia has specific features and outcomes that suggests a unique immunopathogenesis. Severe forms of COVID-19 appear to be more frequent in obese patients, but an association with metabolic disorders is not established. Here, we focused on lipoprotein metabolism in patients hospitalized for severe pneumonia, depending on COVID-19 status. Thirty-four non-COVID-19 and 27 COVID-19 patients with severe pneumonia were enrolled. Most of them required intensive care. Plasma lipid levels, lipoprotein metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
13
0
2
Order By: Relevance
“…Our study found a significant, and very relevant, increase in serum long-chain TG concentrations in COVID-19-positive compared with COVID-19-negative patients. TG are carried in the circulation packed in the very-low density lipoproteins (VLDL), and studies agree in that the levels of triglycerides, VLDL, and polyunsaturated fatty acids are increased in COVID-19 and Ebola virus disease [23] , [58] , [59] , [60] . Therefore, this elevation in long-chain TG concentrations could be related to the immune response, although the mechanisms behind its deregulation are not well elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…Our study found a significant, and very relevant, increase in serum long-chain TG concentrations in COVID-19-positive compared with COVID-19-negative patients. TG are carried in the circulation packed in the very-low density lipoproteins (VLDL), and studies agree in that the levels of triglycerides, VLDL, and polyunsaturated fatty acids are increased in COVID-19 and Ebola virus disease [23] , [58] , [59] , [60] . Therefore, this elevation in long-chain TG concentrations could be related to the immune response, although the mechanisms behind its deregulation are not well elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…There are several reports documenting lipid profiles of plasma in COVID-19 patients emphasizing marked changes in phospholipids, neutral lipids (particularly, triacylglycerols, cholesterol esters) and non-esterified fatty acids related to the severity and transition from the pro-inflammatory to the resolution phases of the disease, as well as in cured patients [77] , [78] , [79] , [80] . In few cases, lipidomics studies were conducted in COVID-19 BAL samples, thus reflecting lipidomics changes in the lungs of intubated patients.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with healthy individuals, patients with dyslipidemia-related diseases are more likely to be infected by SARS-CoV-2 ( 234 , 235 ). Also, SARS-CoV-2 infection caused some COVID-19 patients to have lower serum cholesterol levels (e.g., 27HC, total cholesterol, high density lipoprotein cholesterol, and low-density lipoprotein cholesterol), while triglyceride and non-esterified polyunsaturated fatty acid levels were up-regulated ( Figures 2B-b ) ( 27 , 236 238 ). In particular, decreased serum HDL-C levels are positively correlated with COVID-19 infection severity ( 239 ).…”
Section: The Role Of Cholesterol Metabolism During the Coronavirus Li...mentioning
confidence: 99%